Distribution pattern of ABO and Rh blood groups and their allelic frequencies among different ethnic groups in Malaysia - Amin, Md. Ruhul; Susanto, Dwi; Naher, Laila (Asian Journal of Medical Sciences, 2014)
Background: The experiment involved 4 different racial populations such as Malay (M), Chinese (C), Indian Tamil (I) and confounded population termed as Others (O) from 13 states and 1 federal territory in Malaysia. Methods: A total of 1101 students in Universiti Malaysia Kelantan were surveyed for ABO blood type and Rh factor. Results: Phenotypic frequencies were 0.24, 0.27, 0.09 and 0.40 in M; 0.26, 0.21, 0.06 and 0.38 in C; 0.27, 0.31, 0.09 and 0.33 in I and 0.11, 0.29, 0.09 and 0.51 in O for A, B, AB and O blood group, respectively. Rh+ve cases were found to be abundant and distributed as 0.92, 0.94, 0.89 and 0.79 among M, C, I and O race, respectively. Allele frequencies of IA, IB and i were estimated at 0.17, 0.20 and 0.63 in M; 0.19, 0.16 and 0.65 in C; 0.20, 0.23 and 0.57 in O, respectively. Insignificant χ2 (0.05, 2 = 5.991) interprets that ABO allele frequencies exist in Hardy-Weinberg equilibrium in all races. However, high magnitude of χ2 in M (5.463) signifies continued admixture in the M genetic population or the population is less stable than C and I. C and I are in more stabilized condition in this regard that might be because of closed breeding within them. Conclusion: Results of this study might be useful to blood transfusion services in Malaysia apart from human population geneticists. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11257 Asian Journal of Medical Sciences Vol.6(4) 2015 25-29